Comparative analysis of cell proliferation ratio in plaque and erosive oral lichen planus: An immunohistochemical study - C Pramod Redder; Siddharth Pandit; Dinkar Desai; V Suresh Kandagal; Pramod S Ingaleshwar; Sharan J Shetty; Nupura Vibhute (Wolters Kluwer Medknow Publications, 2014)
Background: Proliferating cell nuclear antigen (PCNA) is a nuclear protein synthesized in the late G1 and S-phase of the cell cycle. Detection of this protein represents a useful marker of the proliferation status of lesions. This study has been carried out to evaluate the cell proliferation rate in oral lichen planus (OLP) and comparison between plaque and erosive lichen planus, which indicates the potential for malignant transformation. Materials and Methods: This study was comprised of 64 cases of histologically proven lichen planus, out of which 32 cases of plaque and erosive each was taken. Two sections were taken from each, one for H and E staining to verify histological diagnosis according to Eisenberg criteria, other sections were stained according to super sensitive polymer horse radish peroxidise method for identifying immunohistochemical expression of PCNA. Data were statistically analyzed by Tukey high-range statistical domain test. Statistically significant P value was considered <0.05. Results: In two types of lichen planus, erosive type (66.86%) showed higher expression of PCNA followed by plaque (17.07%). Overall, P value was <0.001, which was statistically significant. It indicates that proliferation activity is more in erosive lichen planus followed by plaque type, which ultimately results in increased rate of malignant transformation. Conclusion: PCNA is a good nuclear protein marker to evaluate the proliferation status of OLP. Out of the two types of lichen planus, erosive type possesses more proliferative ratio and chances of malignant change is more in this type. It emphasizes the importance of long-term follow-up with erosive type when compared with plaque type.